Zeeman and laser site selective spectroscopy of C1 point group symmetry Sm3+ centres in Y2SiO5: a parametrized crystal-field analysis for the 4f5 configuration. (10th August 2022) - Jobbitt, N L; Wells, J-P R; Reid, M F
Abstract: Parametrized crystal-field analyses are presented for both the six and seven fold coordinated, C1 symmetry Sm 3+ centres in Y2 SiO5, based on extensive spectroscopic data spanning the infrared to optical regions. Laser site-selective excitation and fluorescence spectroscopy as well as Zeeman absorption spectroscopy performed along multiple crystallographic directions has been utilized, in addition to previously determined g tensors for the 6 H5/2 Z1 and 4 G5/2 A1 states. The resultant analyses give good approximation to the experimental energy levels and magnetic splittings, yielding crystal-field parameters consistent with the few other lanthanide ions for which such analyses are available.